2021
DOI: 10.1101/2021.03.11.21253399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunodominant B cell epitope in a hotspot mutation site and mechanism of immune escape for SARS-CoV-2

Abstract: Recent SARS-CoV-2 variants pose important concerns due to their higher transmissibility (1) and escape (2) from previous infections or vaccine-induced neutralizing antibodies (nAb). The receptor binding domain (RBD) of the Spike protein is a major nAb target (3), but data on its B cell epitopes are still lacking. Using a peptide microarray, we identified an immunodominant epitope (S415-429) recognized by 68% of sera from 71 convalescent Brazilians infected with the ancestral variant. In contrast with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…These mutations, located at the interfaces of the RBD-ACE2/antibody complexes, have been shown to increase Spike binding to ACE2 and decrease its recognition by neutralizing antibodies (Nab) (28,(43)(44)(45), leading to the enhanced infection efficacy and transmissibility for the variants. Intriguingly, the same amino acid changes have been shown to alter the corresponding epitopes targeted by neutralizing antibodies (28), thereby providing a potential mechanism of immune escape by reducing or disabling antibody-mediated neutralization (43,(46)(47)(48). Besides the RBD, a P681H mutation located in the S1/S2 linker region of the Spike has been detected in multiple VOC (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…These mutations, located at the interfaces of the RBD-ACE2/antibody complexes, have been shown to increase Spike binding to ACE2 and decrease its recognition by neutralizing antibodies (Nab) (28,(43)(44)(45), leading to the enhanced infection efficacy and transmissibility for the variants. Intriguingly, the same amino acid changes have been shown to alter the corresponding epitopes targeted by neutralizing antibodies (28), thereby providing a potential mechanism of immune escape by reducing or disabling antibody-mediated neutralization (43,(46)(47)(48). Besides the RBD, a P681H mutation located in the S1/S2 linker region of the Spike has been detected in multiple VOC (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA) was performed using 96-well high- binding half-area polystyrene plates coated overnight at 4°C with 4 μg/ml of Spike protein, 2 μg/ml Nucleocapsid protein (NP) (Kindly provided by Dr. Ricardo Gazzinelli, UFMG, Brazil) or 0.8 μg/ml of the RBD domain from SARS-CoV-2 were all expressed in HEK293T cells ( 12 ). In short, 50 µl of diluted sera (1:100) were incubated at 37°C for 45 min.…”
Section: Methodsmentioning
confidence: 99%
“…This interaction seems stronger than the binding between ACE2 and the original main site located at position 501 ( Ferrareze et al ., 2021 ; Nelson et al ., 2021 ). Other studies have shown that 484K reduces neutralization by polyclonal antibodies ( Greaney et al ., 2021 ; Oliveira et al ., 2021 ). Oliveira et al .…”
Section: Discussionmentioning
confidence: 99%